DESENVOLVIMENTO DE SENSORES BIOELETROQUÍMICOS PARA O DIAGNÓSTICO DE DOENÇAS INFECCIOSAS HUMANAS - Erdmann, Cristiane Andreia (2013)
In this work prepared an imunosensor for Chagas disease. This sensor was onstructed by immobilizing the antigen (AG) of Chagas disease under an LbL film between the polyvinyl sulfonate (PVS) and silver nanoparticles incorporated in an inorganic matrix, 3-n-propilpiridíneo silsesquioxane chloride(Ag-SiPy+Cl-) using ITO as the electrochemical probe. The silver nanoparticles were synthesized through chemical reduction using NaBH4 and AgNO3. DLS measurements showed that the suspension of Ag-SiPy+Clconsisted of particles on the order of 20 nm. UV-Vis spectra confirmed the growth of bilayers through the LbL technique using PVS and the suspension Ag-SiPy+Cl- by means of bands at 200 and 260 nm which is referring to the SiPy+Cl- and a band near 400 nm which is referring to the silver nanoparticles. This growth was also demonstrated by AFM technique, which showed that the increase in the number of bilayers leads to an increase in surface roughness and film thickness. The modified films with AG were submitted to the technique electrochemical impedance spectroscopy and showed a pronounced change in impedance in the presence of the antibody (AB) of Chagas disease, indicating that this type of film can be used in a device for the diagnosis of Chagas. Were made tests with different dilutions the samples contaminated with antibody (AB) of Chagas disease and the imunosensor proposed was more sensitive compared to the laboratory test for the qualitative and semi-quantitative of Chagas disease (Gold analyzes Diagnostic Ltd.)